2010
DOI: 10.1371/journal.pone.0013625
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-Like Protein Inclusions in Tobacco Transgenic Plants

Abstract: The formation of insoluble protein deposits in human tissues is linked to the onset of more than 40 different disorders, ranging from dementia to diabetes. In these diseases, the proteins usually self-assemble into ordered β-sheet enriched aggregates known as amyloid fibrils. Here we study the structure of the inclusions formed by maize transglutaminase (TGZ) in the chloroplasts of tobacco transplastomic plants and demonstrate that they have an amyloid-like nature. Together with the evidence of amyloid structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Recently, amyloid adhesins have been proposed to be abundant in natural biofilms produced by a variety of organisms (76,77). Moreover, bacterial inclusion bodies have been proposed to be composed of amyloid (78), and also there have been amyloid-like inclusions observed in plant chloroplasts (79). As more amyloids and their structures are characterized, it is likely that the concept of amyloid will continue to evolve.…”
Section: What Is Amyloid?mentioning
confidence: 99%
“…Recently, amyloid adhesins have been proposed to be abundant in natural biofilms produced by a variety of organisms (76,77). Moreover, bacterial inclusion bodies have been proposed to be composed of amyloid (78), and also there have been amyloid-like inclusions observed in plant chloroplasts (79). As more amyloids and their structures are characterized, it is likely that the concept of amyloid will continue to evolve.…”
Section: What Is Amyloid?mentioning
confidence: 99%
“…Finally, late stages of plant development present alterations in the photosynthetic apparatus, chloroplast ultrastructure, and, particularly, oxidative and antioxidative metabolism pathways are induced (Ortigosa et al 2010). At the same time, the over-expressed TGZ protein, accumulated progressively in chloroplast inclusion bodies (Villar-Piqué et al 2010). These results are discussed in line with chlTGZ involvement in chloroplast functionality.…”
Section: Introductionmentioning
confidence: 74%
“…As we were preparing the present manuscript for submission, a very recent paper reported that the maize transglutaminase can form amyloid-like aggregates in plant cells. 49 Therefore, there is a good possibility that TG2 can form amyloids in a mammalian system.…”
Section: ' Discussionmentioning
confidence: 99%